Clinical and instrumental assessment of herniated discs after nucleoplasty: a preliminary study - Liguori, Alessandro; Galli, Federica; Gurgitano, Martina; Borelli, Anna; Pandolfi, Marco; Caranci, Ferdinando; Magenta Biasina, Alberto M.; Pompili, Giovanni G.M.; Piccolo, Claudia L.; Miele, Vittorio; Masciocchi, Carlo; Carrafiello, Giampaolo (Acta Biomedica Atenei Parmensis, 2018)
Background and Aim: The therapy for low back pain boasts different approaches; one of these is nucleoplasty. We wanted to assess the effectiveness of nucleoplasty both by clinical response both by MR imaging evaluation, including even extrusions larger than one third of the spinal canal. Methods: Fifty-seven patients were treated with nucleoplasty in our hospital, 11 of these patients accepted both clinical and MRI evaluation after six months from treatment. The clinical evaluation was performed with Visual Analogue Scale (VAS) of pain, scored before and after the procedure. MRI evaluation consisted of analysing some imaging parameters of disc protrusions before and after the treatment. Results: In 10 out of 11 (91%) patients, VAS was reduced and only 1 out of 11 (9%) had the same pain after procedure. The mean of decrease of VAS score was 64%. In our population 8/11 (72%) patients had a herniation larger than 1/3 of the sagittal diameter of spinal canal and 100% of them had an improvement with a mean VAS reduction value of 75%. With MRI evaluation, the mean percentage of expulsion before and after treatment was respectively 40% and 34%. The expulsion decreased in 7/13 discs, remained equal in 4/13, and increased in 2/13 discs. Among the 9 larger protrusions, 3 didn’t change, 6 reduced with a decrease mean value of 13%. Other MRI parameters didn’t change significantly. Conclusions: Our preliminary experience supports the success of coblation on pain relief, aiming to show progressively that this treatment is suitable even in case of great extrusions, which are generally treated only with surgical approach. It’s not clear the usefulness of MRI control yet, even if in most of cases we could have found a certain reduction of expulsion degree.